Mathematically modeling worried-well behavior during infectious disease outbreaks - Bismark Singh; Dmitry Gromov (PLoS ONE, 2025)
Although curtailing pathogen spread is critical for mitigating the impact of novel infectious disease outbreaks, addressing the psychological and social responses of populations is also important. This is because uninfected individuals who display an excessive concern of the disease can significantly strain healthcare systems. In existing research, the transmission dynamics of such “worried-well” behavior is largely unexplored. We present a mathematical modeling framework to study such spread alongside the pathogen’s transmission. Our approach extends traditional compartmental models to specifically include the psychological transmission of worry, while acknowledging two extremes of this behavioral response: overly cautious and defiantly protesting. We provide guidance for policymakers, towards healthcare resource allocation and disease outbreak management, by deriving insights into the differential impacts of both these behaviors. Our findings suggest that different strategies are required to manage worried-well surges, depending on the dominant behavioral regime.